A cross-sectional study exploring the sitting time of afghans and other South Asian youth in the UK - Safi, Ayazullah; Khawaja, Irfan; Alkhatib, Ahmad; Collins, Peter; Myers, Tony (Discover public health, 2025)
Abstract Introduction Prolong sitting time (ST) contributes to obesity and numerous Non-Communicable Diseases including type 2 diabetes and cardiovascular diseases. Concerning evidence on young people’s health has reported an increase in ST, the young British South Asians (BSA) is under explored. Thus, the aim of this study was to explore the ST of BSA community, specifically focusing on Afghans, Pakistani, Bangladeshi, and Indian groups. Methods Young BSA from the UK West Midlands region (mean age 15.4 ± 0.5 years) (Total: n = 191, (females: n = 93; males: n = 98) participated in this study. ST was measured based on self-reported total sitting hours using The International Physical Activity Questionnaire—Short Form. Data were modelled using a Bayesian approach to determine differences in ST. Results The findings indicated that the majority of the BSA young people across ethnicities spent prolonged time being sitting. Young people from Indian ethnicity had the highest estimated marginal mean ST (482.23. 95% CI [410.49, 554.73]) and the Afghans the lowest estimated marginal mean ST (344.61, 95% CI [280.22, 411.33]). Discussion This study emphasised a worryingly high percentage of young people from each BSA ethnic group spending prolong ST. To the authors’ knowledge, this is the first study to explore and compare the inter-population differences in ST within BSA minority ethnicities, including Afghan population in the UK. Conclusion The present findings provide a rationale for further scrutiny on key objective and qualitative determinants contributing to ST within different ethnicities among BSA young people.